Improving Kopay Chili Seed Germination Through Priming with Eichhornia crassipes Root Extract - Suwirmen, Suwirmen; Noli, Zozy Aneloi; Emelta, Citra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Kopay chili (Capsicum annuum L. cultivar Kopay) is a local Indonesian cultivar valued for its distinctive flavor, economic potential, and adaptability to tropical climates. However, one of the major challenges in its cultivation is the low and uneven germination rate, which can affect crop uniformity and productivity. This research investigates the effect of priming with water hyacinth (Eichhornia crassipes (Mart.) Solms) root extract on the germination of kopay chili seeds (Capsicum annuum L. cultivar Kopay). The objective was to evaluate the influence of soaking duration, extract concentration, and their interaction on seed germination and early seedling growth. A Completely Randomized Design (CRD) with two factors and three replications was employed. The first factor was soaking duration: 3, 6, 9, and 12 hours; the second factor was extract concentration: 0% (control), 5%, 10%, 15%, and 20%. The results showed that a soaking duration of 3 hours significantly improved germination time, growth rate, vigor index, and root length. Extract concentration alone had no significant effect on any measured parameter. However, the interaction between soaking duration and extract concentration significantly affected germination time, vigor index, root length, and seedling dry weight. These findings suggest that short-term seed priming using water hyacinth root extract can enhance germination and early growth of kopay chili under certain conditions.